Time for micro-RNAs in steatotic liver disease: a case–control study - Stoica, Victor Constantin; Apostol, Dimitri; Diculescu, Mihai Mircea; Gârdan, Iuliana Petronela; Gârdan, Daniel Adrian; Mărunțelu, Ion; Constantinescu, Ileana (Frontiers in Endocrinology, 2024)
One of the challenges of modern day living is to resist to the temptation of overfeeding and sedentariness and maintain a healthy body and mind. On a favorable genetic and epigenetic background, a high fat diet combined with lack of physical exercise constitutes the foundation for severe metabolic disturbances including steatotic liver disease. In our case-control study, we had the aim of establish the role of selected micro-RNAs: miR-122, miR-192, miR-33a and miR-33b as superior biomarkers for the diagnosis and prognosis of steatotic liver in a 36 patients cohort compared to 12 healthy controls. Initial results confirmed the decline in miR-122 expression as fatty liver is progressing. But combinations of ΔmiR's such as ΔmiR33a_192 and ΔmiR33a_122, ΔmiR33b_122 correlate with ultrasound steatosis grade (R 2 = 0.78) while others as ΔmiR33b_122 provide a high specificity and sensitivity in fatty liver disease with an AUC of 0.85. Compared to classical biomarkers, micro-RNAs can be used both for diagnostic and prognostic purposes as their diminished expression in severe cases of steatosis is associated with higher risk of emerging hepatocellular carcinoma. Manipulating micro-RNAs through agomirs or antagomirs can be the answer to the yet unsolved problem of efficient therapy in MAFLD.